التّداوي بالمحرّمات في الفقه الإسلامي - نماذج مختارة - - عامر, لطيفة (University of Eloued-جامعة الوادي, 2016)
This research deals with a so important subject in our life, it is under the title "curing with forbidden materials in "Islamic fight " its goal is to make a spot on the legal decision in having these medicines. This research wants to clarify the notion of curing using these medicines with their different forms and to show the view of "El - fokaha " from these medicines and the wisdom from that. Also, it provides the main ifight problems which related to this subject. This research ends with a set of results and recommendations, the most important is that curing with forbiddinto accounten materials is allowed but with legal regulation which must be take
مذكرة ماستر
Keywords: التداوي بالمحرمات/الفقه الاسلامي; Medicinal taboo/Islamic jurisprudence